2006
DOI: 10.2214/ajr.04.1287
|View full text |Cite
|
Sign up to set email alerts
|

Ferumoxtran-10-Enhanced MR Lymphangiography: Does Contrast-Enhanced Imaging Alone Suffice for Accurate Lymph Node Characterization?

Abstract: On ferumoxtran-10-enhanced MR lymphangiography, contrast-enhanced images alone may suffice for lymph node characterization. However, a certain level of interpretation experience may be required before contrast-enhanced images can be used alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 13 publications
2
61
0
Order By: Relevance
“…Several reports have addressed diagnostic criteria regarding benign and malignant lymph nodes (6,16,17). We found no disagreements between inflammatory nodes and a malignant node overtaken by tumors.…”
Section: Explanation Of Diagnostic Standardssupporting
confidence: 47%
See 2 more Smart Citations
“…Several reports have addressed diagnostic criteria regarding benign and malignant lymph nodes (6,16,17). We found no disagreements between inflammatory nodes and a malignant node overtaken by tumors.…”
Section: Explanation Of Diagnostic Standardssupporting
confidence: 47%
“…The enhancement ratio of lymph nodes were analyzed by T1-weighted values, T2-weighted values, T2* time values, and T2 time values in previous studies (32)(33)(34). Studies have shown that T1SI enhances the fatty hilum of lymph nodes, which may simulate a metastatic deposit in postcontrast T2-weighted images (33).…”
Section: Possible Value Of T2 Enhancement Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…The diffi culty in the detection of lymph nodes by this technique was considered to be due to the fact that the morphology and degree of distension of the stomach changed between the pre-and post-contrast T2*-weighted images, and this occurred likewise for the CT images, which were performed on different days. Harisinghani et al [31] emphasized that, in comparison to T2*-weighted images, T1-and T2-weighted images were more suitable for the identifi cation of lymph nodes because of the high spatial resolution. Therefore, we selected the method in which we detected lymph nodes on postcontrast T1-and T2-weighted images and evaluated them on post-contrast T2*-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that there is no significant difference in diagnostic precision between paired MRI and post-contrast MRI alone for an experienced reviewer (79). In this case, contrast material could be injected in the patient at a site remote from the MR suite, and the patient could return the next day for a single MRI examination.…”
Section: Sentinel Lymph Node Detection With Spio (Interstitial Mr Lymmentioning
confidence: 99%